Utilization of marine by-products for the recovery of value-added products - Fereidoon Shahidi; Vamadevan Varatharajan; Han Peng; Ruchira Senadheera (Journal of Food Bioactives, 2019)
The world fisheries resources have exceeded 160 million tons in recent years. However, every year a considerable amount of total catch is discarded as by-catch or as processing leftovers, and that includes trimmings, fins, frames, heads, skin, viscera and among others. In addition, a large quantity of processing by-products is accumulated as shells of crustaceans and shellfish from marine bioprocessing plants. Recognition of the limited marine resources and the increasing environmental pollution has emphasized the need for better utilization of the by-products. Marine by-products contain valuable protein and lipid fractions, minerals, enzymes as well as many other components. The major fraction of by-products are used for feed production—in making fish meal/oil, but this has low profitability. However, there are many ways in which the fish and shellfish waste could be better utilized, including the production of novel food ingredients, nutraceuticals, pharmaceuticals, biomedical materials, fine chemicals, and other value-added products. In recent times, much research is conducted in order to explore the possible uses of different by-products. This contribution primarily covers the characteristics and utilization of the main ingredients such as protein, lipid, chitin and its derivatives, enzymes, carotenoids, and minerals originating from marine by-products.